(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Phytoplanktons changes were studied at Kpata Lake Lokoja in which transitional period between dry and rainy season were captured including other physicochemical properties of the Lake. The study was perfomed from April to May 2017, where five major phytoplankton groups were recorded. Physicochemical parameters analysed during the study include Electrical conductivity, EC Total dissolved Solid TDS, hardness, DO, BOD, Nitrate-nitrogen Posphate-phosporous and temperature. Electrical conductivity EC and Total dissolved solid TDS were at maximum throughout the study period, while the Temperature was very low in May but remains constant in April and June. The results indicate the changes in phytoplankton groups of the lake and it was influenced by temporal variations observed in the months and anthropogenic activities around the catchment and the banks of the lake. These changes show the relevance of short-term and long term observations of the lake for understanding of variation in phytoplankton groups in a freshwater ecosystem. It is therefore recommended that immediate measures to be taken in order to mitigate the level of pollution of the lake by humans, this could be through enlightenment campaigns, as well as proper monitoring and legislation that will enhance the livelihood of the people and provide them an alternative source of water for their activities, Also need for lake restoration is highly recommended.